The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0244350
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices toward COVID-19 among university students in Japan and associated factors: An online cross-sectional survey

Abstract: The coronavirus disease (COVID-19) pandemic has greatly altered peoples’ daily lives, and it continues spreading as a crucial concern globally. Knowledge, attitudes, and practices (KAP) toward COVID-19 are related to individuals’ adherence to government measures. This study evaluated KAP toward COVID-19 among university students in Japan between May 22 and July 16, 2020, via an online questionnaire, and it further investigated the associated determining KAP factors. Among the eligible respondents (n = 362), 52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
103
4
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(137 citation statements)
references
References 28 publications
18
103
4
4
Order By: Relevance
“…A study from 10 universities in China reported that knowledge of COVID-19 was significantly higher in public universities and among medical majors compared with in private colleges and among non-medical majors [ 22 ]. In contrast other studies from Japan [ 25 ] and India [ 32 ] did not show any differences between medical and non-medical students. The high knowledge about COVID-19 among medical and allied health students in the UAE is similar to findings reported from Japan [ 25 ], Saudi Arabia [ 24 ], Portugal [ 33 ], and Pakistan [ 23 ] (96%, 86%, 82%, 72% respectively).…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…A study from 10 universities in China reported that knowledge of COVID-19 was significantly higher in public universities and among medical majors compared with in private colleges and among non-medical majors [ 22 ]. In contrast other studies from Japan [ 25 ] and India [ 32 ] did not show any differences between medical and non-medical students. The high knowledge about COVID-19 among medical and allied health students in the UAE is similar to findings reported from Japan [ 25 ], Saudi Arabia [ 24 ], Portugal [ 33 ], and Pakistan [ 23 ] (96%, 86%, 82%, 72% respectively).…”
Section: Discussioncontrasting
confidence: 83%
“…University students can be a source of increased health awareness and health education not only for themselves but also for those around them as they take part in the dissemination of pandemic-related knowledge supporting the prevention and control of the pandemic [ 21 , 22 ]. Recent studies from Pakistan, Saudi Arabia and Japan have shown that medical students have sufficient knowledge, positive attitudes, and proactive practices during the COVID-19 crisis [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This contradicting with a study from Japan, where the odd of practices among students from the capital area are more likely than the counterpart. 18 This finding from the current study is suggesting that dissemination of information about Covid-19 has not brought the difference in implementation of prevention, as it is expected that living in rural is easy to access information about prevention than those living in rural.…”
Section: Discussionmentioning
confidence: 52%
“…This finding is supported by a study from Japan, where male sex is positively associated with attitude. 18 But it is opposed by a study from China. 11 None of the studies opposes or supports the rest of the predictors.…”
Section: Discussionmentioning
confidence: 99%
“…The available evidence suggests that this was not the case and instead demonstrates that students were well-informed and complied with the restrictions introduced to curb the spread of Covid-19. 47,48 A national Student Covid Insights Survey undertaken in the last 3 months of 2020 found that 90% of students have followed the rules and this was a similar compliance rate to that self-reported by the general population. 49 These findings paint a more positive picture of students as law-biding citizens and challenge negative portrayals of their attitudes to NPIs, despite extensive scepticism about governmental policies and behaviour.…”
Section: The Pandemic On Campus-physical Health Impacts and Epidemiologymentioning
confidence: 74%